Electrode for capacitor, method for producing same, and electrochemical capacitor

By adding carbon nanotubes of a specific amount and particle size and a specific polymer adhesive to the electrode active material layer of an electrochemical capacitor, the problem of polarizable electrodes peeling off during bending is solved, and the durability and capacitance performance of the electrode are improved.

CN120731472APending Publication Date: 2025-09-30JTEKT CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480012717.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-14
Filing Date
2024-02-09
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

The polarizable electrodes of conventional electrochemical capacitors are easily bent during the manufacturing process, causing the active material layer to separate from the current collector, resulting in a decrease in electrostatic capacitance.

Method used

A specific amount of carbon nanotubes is added to the active material layer of the electrode, the median particle size of the carbon nanotubes is greater than 3.0 μm, and the content is greater than 0.03 mass% and less than 0.50 mass%. A specific polymer is used as a binder to form an electrode composite material to improve the followability and adhesion of the active material layer.

Benefits of technology

It effectively inhibits the peeling of the active material layer on the collector, maintains the electrostatic capacitance of the capacitor, and can maintain high capacity and reduce the increase of internal resistance, especially in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120731472A_ABST
    Figure CN120731472A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode for a capacitor, a method for manufacturing the same, and an electrochemical capacitor. The capacitor electrode (1) has a current collector (11) and an active material layer (12) formed on the current collector (11). The active material layer (12) contains an active material, a binder, and carbon nanotubes. The content of carbon nanotubes in the active material layer (12) is 0.03% by mass or more and 0.50% by mass or less. In addition, the volume-based median diameter of the carbon nanotubes in a dispersion liquid obtained by dispersing the carbon nanotubes in water is 3.0 [mu] m or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a capacitor electrode, a method for producing the same, and an electrochemical capacitor. Background Art

[0002] Electrodes of electrochemical capacitors, such as electric double-layer capacitors and hybrid capacitors, include a current collector and an active material layer formed on the current collector and containing an active material composed of a carbon material. For example, Patent Document 1 describes an electrochemical capacitor having a polarizable electrode primarily composed of a carbon material containing microcrystalline carbon similar to partially oxidized graphite.

[0003] Patent Document 1: Japanese Patent Application Laid-Open No. 2000-331888

[0004] However, there is a problem with the polarizable electrode described in Patent Document 1, which is that it is difficult to deform along with the current collector. Therefore, for example, during the capacitor manufacturing process, if the composite of the polarizable electrode and the current collector is bent by rollers on the production line, or if the composite is wound together with a separator to produce a so-called wound-type unit, there is a concern that the polarizable electrode may easily peel off, resulting in a decrease in electrostatic capacitance. Summary of the Invention

[0005] The present invention has been made in view of the above-mentioned problems, and aims to provide a capacitor electrode including an active material layer that easily deforms along with a current collector, a method for manufacturing the same, and an electrochemical capacitor.

[0006] One embodiment of the present invention is a capacitor electrode comprising: a current collector; and an active material layer comprising an active material, a binder, and carbon nanotubes, and formed on the current collector, wherein the content of the carbon nanotubes in the active material layer is not less than 0.03 mass % and not more than 0.50 mass %, and the volume-based median particle size of the carbon nanotubes in a dispersion obtained by dispersing the carbon nanotubes in water is not less than 3.0 μm.

[0007] Another embodiment of the present invention is an electrochemical capacitor including the capacitor electrode according to the above embodiment.

[0008] Another embodiment of the present invention is a method for manufacturing a capacitor electrode, which is the method for manufacturing a capacitor electrode of the above embodiment, and includes the following steps: mixing the above active material, the above binder, and the above dispersion containing the above carbon nanotubes to prepare an electrode composite material, and coating the above electrode composite material onto the above current collector to form the above active material layer.

[0009] The active material layer of the capacitor electrode (hereinafter referred to as the "electrode") contains an active material, a binder, and the aforementioned specific amount of carbon nanotubes. Furthermore, the carbon nanotubes have a volume-based median diameter within the aforementioned specific range when dispersed in an aqueous dispersion. By incorporating the aforementioned specific carbon nanotubes into the active material layer and maintaining their content within the aforementioned specific range, the active material layer readily deforms with the current collector, and even when the electrode is bent, peeling of the active material layer from the current collector can be suppressed.

[0010] Furthermore, the electrochemical capacitor (hereinafter referred to as "capacitor") includes the aforementioned electrode. Therefore, even when the electrode is bent or wound during capacitor manufacturing, for example, the active material layer can easily deform along with the current collector. This allows the capacitor to minimize capacitance degradation.

[0011] Furthermore, in a method for manufacturing a capacitor electrode, an electrode composite material is prepared by mixing an active material, a binder, and a dispersion of the aforementioned specific carbon nanotubes dispersed in water. This electrode composite material facilitates deformation of the active material layer along with the current collector during the electrode manufacturing process, thereby suppressing separation of the active material layer from the current collector.

[0012] As described above, according to the above embodiment, it is possible to provide a capacitor electrode including an active material layer that easily deforms along with a current collector, a method for manufacturing the same, and an electrochemical capacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a cross-sectional view showing a main portion of the capacitor electrode according to the first embodiment.

[0014] Figure 2 This is an exploded perspective view of the electrochemical capacitor according to the second embodiment.

[0015] Figure 3 This is a partially enlarged cross-sectional view of an electrode wound body according to the second embodiment. DETAILED DESCRIPTION

[0016] (Implementation 1)

[0017] Reference Figure 1 The embodiments of the capacitor electrode of the present invention will be described. Figure 1As shown, the capacitor electrode 1 of this embodiment includes a current collector 11 and an active material layer 12 formed on the current collector 11. In the following description, the term "capacitor electrode" may be simply referred to as "electrode." The active material layer 12 contains an active material, a binder, and carbon nanotubes. The carbon nanotube content in the active material layer 12 is not less than 0.03% by mass and not more than 0.50% by mass. Furthermore, the volume-based median particle size of the carbon nanotubes in the dispersion obtained by dispersing the carbon nanotubes in water is not less than 3.0 μm.

[0018] The electrode 1 of this embodiment is configured to be used in an electrochemical capacitor. More specifically, the electrode 1 can be configured as an electrode for an electric double-layer capacitor. Furthermore, the electrode 1 can be configured as an electrode for a hybrid capacitor such as a lithium-ion capacitor. Furthermore, the electrode 1 can be configured to be used as either the positive electrode or the negative electrode of an electrochemical capacitor.

[0019] As the current collector 11 of the electrode 1, a metal foil having conductivity and made of a metal that is not easily deteriorated when in contact with the electrolyte can be used. For example, aluminum foil, stainless steel foil, copper foil, etc. can be used as the current collector 11 of the electrode 1. In addition, the current collector 11 may be provided with through holes or not. The current collector 11 composed of a metal foil without through holes is cheaper than the current collector 11 composed of a metal foil with through holes. Therefore, by using a metal foil without through holes as the current collector 11, the increase in the material cost of the electrode 1 can be more easily suppressed.

[0020] On the other hand, current collector 11 composed of a metal foil without through-holes tends to have lower adhesion to active material layer 12 than current collector 11 composed of a metal foil with through-holes, and active material layer 12 tends to be easily peeled off from current collector 11. However, the active material layer 12 of this embodiment contains the above-mentioned specific carbon nanotubes, so it is possible to further improve the adhesion to current collector 11. Therefore, even when a metal foil without through-holes is used as current collector 11 of the above-mentioned electrode 1, peeling of the metal foil from the current collector 11 can be more effectively suppressed.

[0021] Active material layer 12, provided on current collector 11, contains an active material, a binder, and carbon nanotubes. For example, an active material such as activated carbon used in electrochemical capacitors can be used as the active material. The active material content in active material layer 12 can be appropriately set within a range of 30% to 90% by mass relative to the solids content of active material layer 12.

[0022] The binder contained in the active material layer 12 has the function of adhering particles of the active material contained in the active material layer 12. The binder can be selected from polymers used as binders for electrochemical capacitors, depending on the structure and application of the electrode 1. More specifically, styrene-butadiene rubber, polytetrafluoroethylene, and polyvinylidene fluoride can be used as the binder.

[0023] The binder included in the active material layer 12 is preferably a polymer having a RED (Relative Energy Difference) value greater than 1, calculated based on the Hansen Solubility Parameters of an electrolyte solution containing an organic solvent and a lithium salt electrolyte having an imide structure. An active material layer 12 containing such a polymer as a binder can maintain a high capacity even in a high-temperature environment of approximately 85°C, for example, and can suppress increases in internal resistance. However, an active material layer 12 containing such a polymer as a binder has difficulty following the deformation of the current collector 11, so it is desirable to suppress its separation from the current collector 11 when the electrode 1 is bent.

[0024] In contrast, the active material layer 12 of the electrode 1 of this embodiment contains the aforementioned specific carbon nanotubes and can therefore easily deform along with the deformation of the current collector 11. Therefore, even when the electrode 1 of this embodiment uses a binder containing the aforementioned specific polymer, it is possible to suppress the peeling of the active material layer 12 from the current collector 11. Furthermore, in this case, a high capacity can be maintained even in a high-temperature environment, and an increase in internal resistance can be suppressed.

[0025] The Hansen Solubility Parameter (HSP), published by Charles M. Hansen, is composed of three parameters: energy δd due to intermolecular dispersion forces, energy δp due to intermolecular dipole interactions, and energy δh due to intermolecular hydrogen bonding. The HSP can be viewed as a coordinate in three-dimensional space (also known as Hansen space). The distance between the HSP of the electrolyte and the HSP of the polymer in Hansen space can be used to predict the solubility of a polymer in an electrolyte.

[0026] The HSP of the electrolyte can be inferred based on the chemical structure and composition ratio of the components contained in the electrolyte. In addition, the HSP of the polymer can be determined experimentally as follows. First, the polymer is dissolved (mixed) in multiple solvents with known HSPs, and the HSPs of the solvents in which the polymer is dissolved and the HSPs of the solvents in which the polymer is not dissolved are plotted in the Hansen space. The plots of the HSPs of the solvents in which the polymer is dissolved are clustered in a spherical shape in the Hansen space, so it is possible to determine a spherical region in the Hansen space that contains the HSPs of the solvents in which the polymer is dissolved and does not contain the HSPs of the solvents in which the polymer is not dissolved. The coordinates of the center of the spherical region determined in this way are taken as the HSP of the polymer. In addition, the spherical region containing the HSPs of the solvents in which the polymer is dissolved is called a "dissolution sphere", and the radius of the dissolution sphere is called an "interaction radius".

[0027] Specifically, the RED value of a polymer relative to the electrolyte is the ratio, Ra / R0, of the distance Ra between the polymer's HSP and the electrolyte's HSP in Hansen space relative to the polymer's interaction radius, R0. When this RED value is greater than 1, the electrolyte's HSP is located outside the polymer's solubility sphere, i.e., in the same region of Hansen space as the HSP of the solvent, in which the polymer is not soluble. Therefore, when the RED value is greater than 1, it can be inferred that the electrolyte and polymer are difficult to dissolve in each other.

[0028] Furthermore, HSP calculation-assisting software (for example, HSPiP (Hansen Solubility Parameters in Practice)) can be used to calculate the HSP of the electrolyte solution, the HSP of the polymer, and the RED value.

[0029] The binder content in the active material layer 12 can be appropriately set within a range of 1% by mass to 9.97% by mass relative to the solid content of the active material layer 12. If the binder content is too low, there is a concern that the active material layer 12 may peel off from the current collector 11. On the other hand, if the binder content is too high, there is a concern that the conductivity of the active material layer 12 may decrease, leading to an increase in resistance. By setting the binder content in the active material layer 12 within the above-mentioned specific range, an increase in conductor resistance can be avoided and the adhesion between the active material layer 12 and the current collector 11 can be sufficiently improved.

[0030] Active material layer 12 contains carbon nanotubes having a volume-based median diameter of 3.0 μm or greater dispersed in an aqueous dispersion. Adding such carbon nanotubes to active material layer 12 improves the ability of active material layer 12 to conform to deformation of current collector 11, thereby preventing separation of active material layer 12 from current collector 11 even when electrode 1 is bent.

[0031] The volume-based median diameter of the carbon nanotubes in the dispersion is preferably 3 μm or greater. In this case, the ability of the active material layer 12 to follow the deformation of the current collector 11 can be further improved, and even when the electrode 1 is bent, the peeling of the active material layer 12 from the current collector 11 can be more effectively suppressed.

[0032] The volume-based median diameter of the carbon nanotubes in the dispersion is preferably 3 μm or more and 20 μm or less, more preferably 9 μm or more and 20 μm or less, and even more preferably 14 μm or more and 20 μm or less.

[0033] The volume-based median diameter of the carbon nanotubes in the dispersion is the cumulative 50% diameter (d50) of the volume-based particle size distribution of the carbon nanotubes. The volume-based particle size distribution of the carbon nanotubes in the dispersion can be measured using a laser diffraction / scattering particle size distribution analyzer.

[0034] The content of carbon nanotubes in active material layer 12 is not less than 0.03 mass% and not more than 0.50 mass% relative to the solid content of active material layer 12. By setting the content of carbon nanotubes to not less than 0.03 mass% and not more than 0.50 mass% relative to the solid content of active material layer 12, preferably not less than 0.04 mass% and not more than 0.50 mass%, and more preferably not less than 0.05 mass% and not more than 0.50 mass%, the effect of improving the followability of active material layer 12 can be more reliably achieved.

[0035] The carbon nanotube content in active material layer 12 is particularly preferably not less than 0.25 mass % and not more than 0.50 mass % relative to the solid content of active material layer 12. In this case, in addition to improving the followability of active material layer 12, the adhesion between active material layer 12 and current collector 11 can be further improved.

[0036] Furthermore, by setting the carbon nanotube content to 0.03% by mass or more and 0.50% by mass or less, it is possible to easily avoid an excessive increase in the viscosity of the electrode composite material during the production process of the electrode 1. From the perspective of more reliably achieving the above-mentioned effects, the carbon nanotube content is preferably 0.03% by mass or more and 0.45% by mass or less, and more preferably 0.03% by mass or more and 0.40% by mass or less.

[0037] Furthermore, in order to improve the followability of the active material layer 12 and to easily avoid an excessive increase in the viscosity of the electrode composite material during the production process of the electrode 1 , the carbon nanotube content may be set to 0.05 mass % or more and 0.40 mass % or less.

[0038] The carbon nanotubes contained in the active material layer 12 may be single-walled carbon nanotubes or multi-walled carbon nanotubes. The average diameter of the carbon nanotubes can be appropriately selected, for example, from a range of 5 nm to 12 nm. To further improve the ability of the active material layer 12 to follow deformation of the current collector 11, the carbon nanotubes contained in the active material layer 12 are preferably multi-walled carbon nanotubes.

[0039] Active material layer 12 may also contain a conductive additive. Adding a conductive additive to active material layer 12 can further reduce the resistance of active material layer 12 and the resistance at the interface between active material layer 12 and current collector 11. Examples of conductive additives include conductive carbon materials such as carbon black, acetylene black, graphite, and carbon fibers.

[0040] When manufacturing the electrode 1, first, the active material, the binder, and the carbon nanotubes are dispersed in water to form a dispersion to mix and produce an electrode composite material. The concentration of the carbon nanotubes in the dispersion can be appropriately set in the range of 0.1 mass % to 1.0 mass %. From the perspective of making it easier to set the median particle size of the carbon nanotubes in the dispersion to a desired range, the concentration of the carbon nanotubes in the dispersion is preferably 0.2 mass % to 0.7 mass %.

[0041] In addition to the carbon nanotubes and water as a dispersion medium, the dispersion may also contain additives such as a dispersant. Examples of dispersants include carboxymethyl cellulose and sodium dodecylbenzenesulfonate. The concentration of the dispersant in the dispersion can be appropriately set within a range of, for example, 0.1% by mass to 1.0% by mass. From the perspective of more easily setting the median particle size of the carbon nanotubes in the dispersion to a desired range, the dispersant is preferably carboxymethyl cellulose.

[0042] In addition, solvents and thickeners can be added to the electrode composite material as needed to adjust the viscosity of the electrode composite material. Water or the like can be used as a solvent. In addition, carboxymethyl cellulose or the like can be used as a thickener. The viscosity of the electrode composite material can be appropriately set within a range of 1000 mPa·s to 10000 mPa·s. In addition, the viscosity of the electrode composite material is measured using a rheometer at 2s -1 The value obtained when measuring the shear rate.

[0043] Next, the electrode composite material is applied to one or both sides of the current collector 11 to form an active material layer 12. The electrode composite material can be applied using a known coating device such as a knife coater or a die coater. The thickness of the active material layer 12 can be set to, for example, 1 mg / cm2 of mass per unit area of ​​the active material. 2 More than 5mg / cm 2 The following will do.

[0044] After the active material layer 12 is formed on the current collector 11 , the active material layer 12 may be dried as needed to remove the solvent and the like in the active material layer 12 . In this way, the electrode 1 can be obtained.

[0045] The active material layer 12 of the electrode 1 of the present embodiment can easily deform along with the current collector 11 even when the current collector 11 is bent, and thus can suppress separation of the active material layer 12 from the current collector 11 .

[0046] (Implementation Method 2)

[0047] In this embodiment, an example of an electrode configured as a positive electrode of a lithium ion capacitor and a capacitor including the electrode is described. Furthermore, in the reference numerals used in this embodiment and thereafter, unless otherwise specified, components denoted by the same reference numerals as those used in the previously described embodiment represent the same structural components, etc., as those in the previously described embodiment.

[0048] like Figure 2 As shown, the lithium ion capacitor 2 of this embodiment includes an electrode wound body 3 composed of a stack 30 of a positive electrode, a negative electrode, and a separator; an outer package 21 that houses the electrode wound body 3; and a positive electrode terminal 211p and a negative electrode terminal 211n provided on the outer package 21. The positive electrode terminal 211p is electrically connected to the positive electrode of the electrode wound body 3 via a positive electrode lead 313p, and the negative electrode terminal 211n is electrically connected to the negative electrode of the electrode wound body 3 via a negative electrode lead 313n. Furthermore, the separator 32 is impregnated with an electrolyte solution containing lithium ions and counter anions.

[0049] The shape of the unit cell of the lithium ion capacitor 2 is not particularly limited, and various forms such as cylindrical, square, and laminated can be adopted. Figure 2 As shown, the cell shape of the lithium ion capacitor 2 of this embodiment is a laminated type, and the electrode wound body 3 is enclosed between two outer packaging materials 21 .

[0050] like Figure 3 As shown, the stack 30 constituting the electrode winding 3 includes: a positive electrode 31p, a first separator 32a stacked on the positive electrode 31p, a negative electrode 31n stacked on the first separator 32a, and a second separator 32b stacked on the negative electrode 31n. The electrode winding 3 is formed by winding the stack 30.

[0051] The structure of the positive electrode 31p of this embodiment is the same as that of the capacitor electrode 1 of the first embodiment. More specifically, the positive electrode 31p includes a positive electrode current collector 311p and a positive electrode active material layer 312p provided on the positive electrode current collector 311p. The positive electrode current collector 311p is the same as the current collector 11 of the electrode 1 of the first embodiment and is made of a metal foil. The metal foil is made of a metal that is conductive and is not easily deteriorated when in contact with the electrolyte. In addition, as Figure 2 As shown, the positive electrode current collector 311p is provided with a positive electrode lead 313p for electrically connecting the positive electrode current collector 311p and the positive electrode terminal 211p.

[0052] Like the active material layer 12 of the electrode 1 in the first embodiment, the positive electrode active material layer 312 p includes activated carbon as a positive electrode active material, a binder, and carbon nanotubes having a median diameter within the above-specified range in a dispersion.

[0053] The first separator 32a and the second separator 32b are interposed between the positive electrode 31p and the negative electrode 31n in the electrode winding 3, and the positive electrode 31p and the negative electrode 31n are electrically insulated by the separator 32. The first separator 32a and the second separator 32b can be made of, for example, a porous sheet made of a polymer such as a polyolefin resin or cellulose.

[0054] The electrolyte solution impregnated in the first separator 32 a and the second separator 32 b contains at least an electrolyte including lithium ions and counter anions, and a solvent.

[0055] As the solvent of the electrolyte, organic solvents such as carbonate organic solvents, nitrile organic solvents, lactone organic solvents, ether organic solvents, alcohol organic solvents, ester organic solvents, amide organic solvents, sulfonic acid organic solvents, ketone organic solvents and aromatic organic solvents can be used. The above organic solvents can be used alone or in combination of two or more organic solvents.

[0056] Examples of carbonate-based organic solvents that can be used include cyclic carbonates such as vinylene carbonate, propylene carbonate, and vinylene fluorocarbonate; and chain carbonates such as ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate.

[0057] Examples of nitrile organic solvents include acetonitrile, acrylonitrile, adiponitrile, succinonitrile, and isobutyronitrile. Examples of lactone organic solvents include γ-butyrolactone and γ-valerolactone. Examples of ether organic solvents include cyclic ethers such as tetrahydrofuran and dioxane, and chain ethers such as 1,2-dimethoxyethane, dimethyl ether, and triethylene glycol.

[0058] Examples of alcohol organic solvents include ethanol and ethylene glycol. Examples of ester organic solvents include carboxylates such as methyl formate and propyl propionate, phosphates such as trimethylphosphate, sulfates such as dimethylsulfate, and sulfites such as dimethylsulfite.

[0059] Examples of amide organic solvents include N-methyl-2-pyrrolidone and ethylenediamine. Examples of sulfonic acid organic solvents include chain sulfonic acids such as dimethylsulfonic acid and cyclic sulfonic acids such as 3-sulfonylbenzene. Examples of ketone organic solvents include methyl ethyl ketone. Examples of aromatic organic solvents include toluene.

[0060] The solvent used in the electrolyte preferably contains a carbonate organic solvent. Carbonate organic solvents have excellent oxidation resistance within the voltage range assumed during use of the lithium ion capacitor 2. Therefore, by using a carbonate organic solvent as the solvent of the electrolyte, oxidation of the electrolyte can be suppressed for a longer period of time.

[0061] In addition, the solvent that is more preferably used for the electrolyte contains cyclic carbonate, must contain cyclic carbonate, and more preferably also contains one or more organic solvents selected from the group comprising chain carbonate, nitrile organic solvents, lactone organic solvents, ether organic solvents, alcohol organic solvents, ester organic solvents, amide organic solvents, sulfonic acid organic solvents, ketone organic solvents and aromatic organic solvents, further preferably contains cyclic carbonate and chain carbonate, particularly preferably contains ethyl methyl carbonate as cyclic carbonate and diethyl carbonate as chain carbonate.

[0062] By using an electrolyte solution that essentially contains a cyclic carbonate, the viscosity of the electrolyte solution can be lowered and the degree of electrolyte dissociation can be further increased. As a result, the ion conductivity can be further increased, and the internal resistance of the lithium ion capacitor 2 can be further reduced.

[0063] Furthermore, by using vinylene carbonate as the cyclic carbonate, a solid electrolyte interface (SEI) film can be formed on the surface of the negative electrode 31n. This makes the negative electrode 31n less likely to be directly exposed to the potential of lithium, thereby further improving the oxidation resistance of the electrolyte.

[0064] The electrolyte solution contains an electrolyte containing lithium ions and counter anions. As the counter anion, for example, an anion having an imide structure such as a bis(fluorosulfonyl)imide anion, a bis(trifluoromethanesulfonyl)imide anion, or a bis(pentafluoroethanesulfonyl)imide anion can be used, but is not limited to the above anions. The concentration of the electrolyte in the electrolyte solution can be appropriately set within a range of, for example, 0.5 mol / L to 10.0 mol / L.

[0065] Furthermore, the electrolyte solution may contain additives such as vinylene carbonate.

[0066] The negative electrode 31n of the wound electrode body 3 includes a negative electrode current collector 311n and a negative electrode active material layer 312n formed on the negative electrode current collector 311n. Like the positive electrode current collector 311p, the negative electrode current collector 311n is made of a conductive metal foil that is resistant to deterioration when exposed to the electrolyte. Furthermore, a negative electrode lead 313n is provided on the negative electrode current collector 311n to electrically connect the negative electrode current collector 311n to the negative electrode terminal 211n.

[0067] The negative electrode active material layer 312n contains at least a negative electrode active material and a binder. For example, a conductive carbon material such as graphite can be used as the negative electrode active material. Furthermore, the binder for the negative electrode active material layer 312n can be, for example, styrene-butadiene rubber, polytetrafluoroethylene, and polyvinylidene fluoride. Specifically, the binder for the negative electrode active material layer 312n in this embodiment is styrene-butadiene rubber. Alternatively, the capacitor electrode 1 of Embodiment 1 can be used as the negative electrode 31n.

[0068] (Experimental Example 1)

[0069] In this example, the durability of electrodes produced by varying the median diameter and amount of carbon nanotubes added was evaluated. The following describes the method for producing the electrodes and the method for evaluating their durability against bending.

[0070] <Electrode Production Method>

[0071] First, carboxymethyl cellulose, carbon nanotubes, and water were mixed to prepare a dispersion of carbon nanotubes. An electrode composite material was prepared by mixing this dispersion with activated carbon, acetylene black as a conductive additive, and a binder. The acetylene black content in the electrode composite material was set to 15% by mass based on the solids content of the electrode composite material.

[0072] As shown in Table 1, the binder used in this example contains either polymer A or polymer B. Both polymers A and B exhibit RED (Relative Energy Difference) values ​​greater than 1, calculated based on Hansen Solubility Parameters, for an electrolyte solution containing an organic solvent and a lithium salt electrolyte having an imide structure. The polymer content relative to the solids content of the electrode composite material is shown in Table 1.

[0073] The carbon nanotubes used in this example are multi-walled carbon nanotubes having an average diameter of 8.5 nm. Furthermore, as described above, the dispersion contains carbon nanotubes, water as a dispersion medium, and carboxymethyl cellulose as a dispersant. The concentration of the carbon nanotubes in the dispersion is 0.4% by mass, and the concentration of the carboxymethyl cellulose is 0.4% by mass. Furthermore, the median particle size of the carbon nanotubes in the dispersion and the amount contained relative to the solid content of the electrode composite material are shown in Table 1. Furthermore, the median particle size of the carbon nanotubes is the cumulative 50% diameter of the volume-based particle size distribution obtained by measuring the dispersion using a laser diffraction / scattering particle size distribution analyzer.

[0074] Next, a 15 μm thick aluminum foil without through-holes was used as a current collector, and one of the electrode composite materials shown in Table 1 was applied to one side of the current collector to form an active material layer. The amount of electrode composite material applied was adjusted so that the mass of activated carbon per unit area contained in the active material layer became 1.8 mg / cm 2 After the active material layer was formed on the current collector, the active material layer was dried to remove water, etc. In this way, test pieces A1 to A10 and test piece C1 shown in Table 1 were obtained.

[0075] In addition, test specimens B1 to B2 shown in Table 1 were used for comparison with test specimens A1 to A10, and test specimen D1 was used for comparison with test specimen C1. Test specimen B1 had the same structure as test specimens A1 to A10, except that the active material layer did not contain carbon nanotubes. Test specimen B2 had the same structure as test specimens A1 to A10, except that the median particle size of the carbon nanotubes was different. Test specimen D1 had the same structure as test specimen C1, except that the active material layer did not contain carbon nanotubes.

[0076] <Evaluation method for durability against bending>

[0077] To evaluate bending durability, a cylindrical mandrel with a diameter of 5 mm, 6 mm, 8 mm, or 10 mm was used. First, one end of the test piece was fixed, and the other end was held, positioning the test piece in a generally horizontal position. In this position, the mandrel was placed between one and the other ends of the test piece and wound around it, with the test piece wrapping half a circle around the mandrel. The appearance of the portion of the test piece wrapped around the mandrel was then visually observed.

[0078] In the "Durability against Bending" column of Table 1, the symbol "A" is recorded when the appearance of the active material layer does not change before and after the test body is wound on each core shaft, the symbol "B" is recorded when cracks occur in the active material layer after the test body is wound on the core shaft, and the symbol "C" is recorded when the active material layer is peeled off from the collector after the test body is wound on the core shaft.

[0079] [Table 1]

[0080] [Table 1]

[0081] (Table 1)

[0082]

[0083] As shown in Table 1, the active material layers of test specimens A1 to A10 contained carbon nanotubes whose median particle size in the dispersion fell within the aforementioned specific range. Therefore, compared to test specimen B1, which had the same structure except for not containing carbon nanotubes, and test specimen B2, which had a median particle size of carbon nanotubes outside the aforementioned specific range, these test specimens more readily followed the deformation of the current collector. Even with a reduced radius of curvature of the portion wound around the mandrel, cracking in the active material layer and separation of the active material layer from the current collector were suppressed.

[0084] In comparison with test pieces C1 and D1 having the same structure except for the presence or absence of carbon nanotubes, it can be understood that the active material layer of test piece C1 containing carbon nanotubes is more likely to follow the deformation of the current collector than that of test piece D1 not containing carbon nanotubes.

[0085] (Experimental Example 2)

[0086] In this example, the 90° peel strength of the active material layer of electrodes fabricated by varying the median diameter and amount of carbon nanotubes added was evaluated. The following describes the electrode fabrication method and the evaluation method for its durability against bending.

[0087] <Electrode Production Method>

[0088] The electrodes of this example (test pieces E1 to E14) had the same structure as test pieces A1 to A10 of Experimental Example 1, except that the type and content of carbon nanotubes were changed as shown in Table 2. The method for preparing test pieces E1 to E14 was the same as that for test pieces A1 to A10 of Experimental Example 1, except that the type and content of carbon nanotubes were changed as shown in Table 2.

[0089] <90° peel strength measurement method>

[0090] First, a double-sided tape is attached to the surface of the current collector of the test body. The test body is fixed on the sliding workbench by attaching the double-sided tape to the sliding workbench of the 90° peel tester. Next, a sticky tape is attached to the active material layer of the test body. Then, one end of the sticky tape is pulled up at a speed of 10 mm / min so that the angle relative to the active material layer is 90°, and the active material layer is peeled off from the current collector, and the load required for the peeling of the active material layer is measured. The operation is performed four or more times for each test body, and the average value of the four measurements is divided by the width of the sticky tape, and the 90° peel strength (unit: N / cm) of the active material layer is recorded in Table 2.

[0091] [Table 2]

[0092] (Table 2)

[0093]

[0094] As shown in Table 2, test pieces E9 and E13 containing relatively high carbon nanotube contents and test piece E14 using carbon nanotubes having a large median diameter had higher 90° peel strength and better adhesion to the current collector than other test pieces.

[0095] The present invention is not limited to the above-described embodiments, but can be applied to various embodiments within the scope of the gist of the invention.

[0096] This application is based on Japanese Patent Application No. 2023-020718 filed on February 14, 2023, and the contents are incorporated herein by reference.

Claims

1. A capacitor electrode comprising: a current collector; and an active material layer comprising an active material, a binder and carbon nanotubes and formed on the current collector; The content of the carbon nanotubes in the active material layer is 0.03 mass % or more and 0.50 mass % or less. The volume-based median diameter of the carbon nanotubes in a dispersion obtained by dispersing the carbon nanotubes in water is 3.0 μm or more.

2. The capacitor electrode according to claim 1, wherein The current collector is a metal foil having no through-holes.

3. The capacitor electrode according to claim 1 or 2, wherein The binder includes a polymer having a RED value greater than 1 calculated based on Hansen solubility parameters for an electrolyte solution including an organic solvent and a lithium salt electrolyte having an imide structure.

4. An electrochemical capacitor comprising: The capacitor electrode according to claim 1 or 2.

5. The electrochemical capacitor according to claim 4, wherein The electrochemical capacitor includes an electrode wound body formed by winding a laminate of the capacitor electrode and the separator.

6. A method for producing a capacitor electrode, the method for producing a capacitor electrode according to claim 1 or 2, comprising the following steps: The active material, the binder, and the dispersion containing the carbon nanotubes are mixed to prepare an electrode composite material. The active material layer is formed by applying the electrode composite material onto the current collector.

Citation Information

Patent Citations

  • Electrochemical capacitor

    JP2000331888A

  • Method for producing fatty acid particulate

    JP2023020718A